Individanpassad Marknadsföring -Uppskattat eller ett hot mot konsumenters integritet? - Hallner,Anna; Berggren,Sofie; Ströberg,Yasmine (2016)
Title: Personalized Marketing- do consumers appreciate it or is it a threat against integrity? Seminar date: 2016-01-15 Course: FEKH29, Degree Project Undergraduate level, Business Administration, Undergraduate level, 15 University Credits Points (UPS) Authors: Sofie Berggren, Anna Hallner & Yasmine Ströberg Advisor: Magnus Lagnevik Key words: Personalized marketing, CRM, buying behavior, integrity, Facebook Purpose: The purpose of this paper is to investigate how consumers perceive personalized marketing on Facebook and how it affects their buying behavior online. The thesis focuses on consumer’s attitudes, preferences and behavior while being exposed to this kind of advertising. Methodology: A qualitative approached research through raw data from four semi-structured focus groups and secondary data derived from scientific publications. This approach is deductive while containing inductive elements. Theoretical perspectives: The theoretical framework is based on basic theories within CRM, consumers buying behavior and personal integrity. Empirical foundation: The empirical foundation is based on discussions in four focus groups with a total of 20 respondents, both women and men in various ages, who all are active users on the social media platform Facebook. Conclusions: The study reveals that personalized marketing on Facebook can be seen as positive if it matches each consumer’s preference and may then result in a purchase. This conclusion mainly refer to the younger generation since they are more impulsive in their buying behavior online, while the older population generally don’t like advertising at all on social media platforms. Consumers can be annoyed if companies fail to analyze their customers accurate and if they advertise irrelevant products or things they’ve already bought. The study shows further on that the majority doesn’t feel concerned about their personal identity on Facebook, even if some of them find it frightening that the social media platform knows a lot about them.
Keywords: Facebook; integritet; köpbeteende; Individanpassad marknadsföring: CRM